Penerapan Model Pembelajaran Kooperatif Tipe Team Games Tournament (TGT) Untuk Meningkatkan Prestasi Belajar PKn Siswa Kelas VIIF SMP Negeri 1 Abang - I Nyoman Duduk (Cetta: Jurnal Ilmu Pendidikan, 2019)
The aim of this class room research which was done at class VII F of the first year students of SMP Negeri 1 Abang academic Year 2017/2018 is to improve achievement of learning Civics by using Team Game Tournament (TGT) Cooperative Metod. The result data of this research was collected by giving achievement test. The data were analyzed descriptively. The result of this research consist of first data , cycle 1, and cycle 2. The first data showed the mean of the class was only 71,29% and Minimum Learning Creteria was 48.38%. This data was far from expectation since Minimum Learning Creteria of Civics in this School was 75.00% . In cycle 1 the mean of the class reached 73.22% and the presentage of Minimum Learning Criteria was 58.06%. In cycle 2 the mean of the class had been reached 82.90% and the presentage of Minimum Learning Criteria was reached 87.09%. This data in cycle 2 was an expected data as the eeffect of using Constructive Teaching and Learning Metod. The conclussion was Team Game Tournament (TGT) Cooperative Type Metod can encrease the student achievement of learning.